Introduksi Teknologi DNA Barcoding kepada Staf UPTD Perikanan Budidaya Air Payau dan Laut Karang Intan: Introduction of DNA Barcoding Technology to UPTD Staff of Brackish and Marine Aquaculture Karang Intan - Sasmita, Rani; Hidayaturrahmah, Hidayaturrahmah; Badruzsaufari, Badruzsaufari; Firnanda, Muhammad Riyan; Fitri, Muhammad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Partners in community service activity are UPTD Brackish and Marine Aquaculture, Karang Intan, one of the centers under South Kalimantan Province that specializes in the hatchery of local fish such as snakehead (Channa striata), common carp (Cyprinus carpio), and climbing perch (Anabas testudineus). The problem in the partner is fish farming that still relies on seeds from nature, which causes several problems, such as slow seed growth, decreased production quality, disease attacks and hereditary abnormalities that are getting higher due to interbreeding. Based on these problems, the team collaborated with the UPTD for Brackish and Marine Aquaculture, Karang Intan, to improve the genetic quality of fish by introducing DNA barcoding techniques, especially at the spawning stage. The introduction of DNA barcoding technology is carried out through (1) classical counseling and group discussions, 2) training and assistance covering technical aspects of DNA barcoding (fish DNA isolation, DNA amplification, visualization of PCR products with electrophoresis, to the sequencing). Based on the evaluation, 100% of the participants were enthusiastic and realized the importance of DNA barcoding techniques to produce superior broodstock and fish fry, especially for snakehead, common carp, and climbing perch commodities.